KEBIJAKAN KEMENTERIAN AGAMA DALAM PELAYANAN PENDIDIKAN AGAMA KELOMPOK MINORITAS - Aji Sofanudin (Balai Penelitian dan Pengembangan Agama Jakarta, 2019)
This study aims to review the results of the research by The Office of Religious Research and Development Semarang about The Implementation of Religious Education in Minority Group. The research findings show that although the regulation of religious education services for minority groups has a strong foundation but in its implementation not all schools can serve religious education for minority groups. Based on the study it was found that (1) there were schools that provided all of religious education services according to the students needs;(2) there are schools that only provide one religious education service, and (3) there are also schools that provide a portion of minority religious education services. Judging from the suitability of religious education services with regulations found there are still those that are not in accordance with PMA Number 16 of 2010.